2016
DOI: 10.1016/j.biomaterials.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Artificial bacterial biomimetic nanoparticles synergize pathogen-associated molecular patterns for vaccine efficacy

Abstract: Antigen-presenting cells (APCs) sense microorganisms via pathogen-associated molecular patterns (PAMPs) by both extra- and intracellular Toll-like Receptors (TLRs), initiating immune responses against invading pathogens. Bacterial PAMPs include extracellular lipopolysaccharides and intracellular unmethylated CpG-rich oligodeoxynucleotides (CpG). We hypothesized that a biomimetic approach involving antigen-loaded nanoparticles (NP) displaying Monophosphoryl Lipid A (MPLA) and encapsulating CpG may function as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…CD40, CD80 and CD86) and upregulation of immunoregulatory genes (e.g. Cxcl1, Ccl4, Il6 and Cd14) [65-]. Narasimhan et al have shown that amphiphilic polyanhydride NPs possess pathogen-mimicking properties, and can activate DCs similarly to LPS (TLR 4 agonist) [68].…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%
See 1 more Smart Citation
“…CD40, CD80 and CD86) and upregulation of immunoregulatory genes (e.g. Cxcl1, Ccl4, Il6 and Cd14) [65-]. Narasimhan et al have shown that amphiphilic polyanhydride NPs possess pathogen-mimicking properties, and can activate DCs similarly to LPS (TLR 4 agonist) [68].…”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%
“…Similarly, when nanoporous silicon NPs were coated with cellular membranes purified from leukocytes, these “camouflaged” NPs could avoid opsonization, delay uptake by the mononuclear phagocyte system, preferentially bind inflamed endothelium, and facilitate accumulation in a tumor site [81]. In addition, CpG and MPLA coated NPs, known as “artificial bacteria”, demonstrated stronger pro-inflammatory response (higher IL-6 and IL-12 secretion) [65]. Taking advantage of the physical properties of NPs, superparamagnetic iron oxide NPs can be efficiently recognized and uptaken by DCs in vitro, while simultaneously acting as an imaging agent for magnetic resonance imaging (MRI) in vivo [82].…”
Section: Therapeutic Immune Modulation By Engineered Nanoparticlesmentioning
confidence: 99%
“…Triggering a combination of TLRs in APCs can have synergistic effects. The simultaneous delivery of MPLA, CpG ODN and the model antigen OVA loaded on 200 nm PLGA particles induces a strong immune response against the model antigen in a mouse model [66]. The localization of the immunopotentiator seems to be a crucial point for vaccine adjuvant design.…”
Section: Nanodelivery Of Immunopotentiatorsmentioning
confidence: 99%
“…The stimulation of humoral and antigen-specific T cell responses is enhanced when CpG is encapsulated, compared to its adsorption at the surface of the nanoparticulate vector, showing the interest of mimicking the biology of the pathogens. The stimulation of TLR4 and TLR9 has a synergistic effect when co-delivered in the same particle, especially for cytotoxic response after vaccination in a mouse model [66]. A synergistic increase in the antigen-specific humoral response is observed after the immunization of mice with 300 nm PLGA NPs containing the TLR4 ligand MPL and the TLR7 ligand R837 compared with the molecular adjuvants alone [67].…”
Section: Nanodelivery Of Immunopotentiatorsmentioning
confidence: 99%
“…Delivery systems that localize and/or amplify the effects of immunomodulators have great potential for the treatment of leishmaniasis. Nanoparticles (NPs), usually solid polymeric or liposomal spheres, have been extensively demonstrated as effective in drug delivery and vaccine applications [14], and these particles possess uniquely beneficial features for anti-parasitic therapy [15, 16]. Phagocytic cells, including macrophages and dendritic cells (DCs), express TLRs and efficiently endo-, phago-, and pinocytose NPs in the size range of 50–500 nanometers (nm), enabling high intracellular concentrations of NP encapsulants that are protected from degradation and shielded to limit non-specific immune activation [17].…”
Section: Introductionmentioning
confidence: 99%